THE ESTIMATION OF FLOOD-AFFECTED AREA IN THE DOWNSTREAM OF CODE RIVER, YOGYAKARTA, INDONESIA - Suhadi Purwantara; Arif Ashari; Dyah Respati Suryo Sumunar; Nurul Khotimah (Universitas Negeri Medan, 2022)
The rapid development of settlements and sediment deposition has increasingly narrowed the drainage in the Code River. This condition causes floods and wider distribution of the affected areas. This research aims to estimate the maximum amount of rain, predict the probability of flood, and predict flood-prone areas in the Code River. Data were collected by observation, remote sensing image interpretations, literature studies, and documentation. Data analysis was performed using Log Pearson Type III for design rainfall analysis, Weibull formula for flood probability analysis, and rational method for planning maximum discharge analysis. Flood modeling is carried out by the iteration method. The results show: (1) the maximum amount of rain based on the calculated design rainfall with a return period of 5 to 40 years is R5 = 106.83 mm, R10 = 116.67 mm, R20 = 127.30 mm, R40 = 134.25 mm, (2) the probability of flood that is predicted from the maximum discharge caused by the design rainfall at each return period is Q5 = 82.45 m3/sec, Q10 = 89.42 m3/sec, Q20 = 96.95 m3/sec, Q40 = 101.86 m3/sec. (3) Inundation of the flood target area in the 5-year return period covers an area of 0.4456 km2, the 10-year return period covers 0.5209 km2, the 20-year return period covers 0.6023 km2, the 40-year return period covers 0.6555 km2. This paper presents information on the potential for a flood at various return periods to increase preparedness and reduce risks due to flood disasters.Keywords: Disaster, Floods, Estimated Flood-Affected Areas, Code River, Yogyakarta